Pemahaman pembelajaran bahasa arab ditinjau dari sudut pandang teori kognitif piaget dan vygotsky - Husniyah, Lina (Maliki Interdisciplinary Journal, 2025)
The understanding of Arabic language learning through the cognitive theories of Piaget and Vygotsky. Piaget emphasizes the importance of adjusting material to the cognitive development stages of students, ranging from the sensorimotor to the formal operational stage, which affects the understanding of grammatical abstraction. Meanwhile, Vygotsky highlights the role of social interaction and scaffolding in learning, where a collaborative environment aids students in grasping language concepts. Vygotsky’s concept of the Zone of Proximal Development (ZPD) underscores the necessity of teacher support to help students reach their learning potential. This study will analyze the challenges and potentials in Arabic language learning, as well as practical implications for effective learning strategies. Additionally, internal and external factors such as motivation, learning styles, and learning environments will be examined. The findings are expected to provide recommendations for teachers and policymakers to enhance the effectiveness of Arabic language education in Indonesia